A new strategy for 2, 4, 6-Trinitrotoluene adsorption and electrochemical reduction on poly(melamine)/graphene oxide modified electrode. (1st December 2015) - Cotchim, Suparat; Thavarungkul, Panote; Kanatharana, Proespichaya; Limbut, Warakorn
Graphical abstract: Highlights: A new fabrication strategy of a poly(melamine)/graphene oxide (PM/GO) modified glassy carbon electrode (GCE) (PM/GO/GCE) for the detection of ultra-traces of TNT is proposed. The PM/GO/GCE exhibits excellent adsorption and electrochemical reduction of TNT via the AdCSV technique. The PM/GO/GCE provides for a high sensitivity, good repeatability and selectivity. This strategy opens new opportunities for the sensitive detection of TNT aiming at protection of the environmental and homeland securities. Abstract: A poly(melamine)/graphene oxide (PM/GO) layer modified on a glassy carbon electrode (GCE) was used for the adsorption and electrochemical detection of 2, 4, 6 trinitrotoluene (TNT). The surface morphology and electrochemical behaviour of the PM/GO/GCE were characterized by scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FT-IR), cyclic voltammetry (CV) and adsorptive cathodic stripping voltammetry (AdCSV). The PM/GO/GCE exhibited excellent adsorption and electrochemical reduction of TNT via the AdCSV technique with two linear ranges, 1–90 μg L −1 and 100–1000 μg L −1, a detection limit of 0.34 μg L −1 and a quantitation limit of 1.14 μg L −1 . The PM/GO/GCE provided for a high sensitivity, good repeatability and selectivity. This modified electrode was successfully applied to detect TNT in soil samples with good recoveries that ranged from 93 to 99%.